Vanadium(IV)-Chlorodipicolinate Protects against Hepatic Steatosis by Ameliorating Lipid Peroxidation, Endoplasmic Reticulum Stress, and Inflammation - Yuanli Wang; Rulong Chen; Jingyi Li; Guodong Zeng; Juntao Yuan; Jingran Su; Chunyan Wu; Zhongbing Lu; Fang Zhang; Wenjun Ding (MDPI AG, 2022)
Non-alcoholic fatty liver disease (NAFLD) is increasingly prevalent and represents a growing challenge in terms of prevention and treatment. The aim of this study is to investigate the protective effects and the underlying mechanisms of vanadium(IV)-chlorodipicolinate ([VIVO(dipic-Cl)(H2O)2, VOdipic-Cl]) in a mouse model of NAFLD induced by a high-fat diet (HFD). VOdipic-Cl (10 mg/kg/day body weight) treatment for 4 weeks significantly controlled body weight gain, and effectively reduced the increase in serum and hepatic triglyceride (TG) and total cholesterol (TC) levels, mitigated pathological injury, decreased malondialdehyde (MDA) level, and inhibited endoplasmic reticulum (ER) stress and inflammatory response in the livers of C57BL/6 obese mice. Moreover, RNA-sequencing analysis revealed distinct transcriptional profiles with differentially expressed genes (DEGs) in livers. We found that VOdipic-Cl effectively down-regulated genes related to lipid synthesis and up-regulated genes related to fatty acid transport and lipolysis, and down-regulated the expression of genes related to ER stress and immune response in the livers of obese mice. In conclusion, VOdipic-Cl effectively prevented hepatic steatosis by controlling body weight, mitigating oxidative stress, and regulating the expression of genes related to lipid metabolism, ER stress and immune response, which provides new insights into the molecular mechanism of the protective effect of VOdipic-Cl against hepatic steatosis.